2009
DOI: 10.1111/j.1365-3083.2008.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Nervous Systems Share Molecular and Functional Similarities: Memory Storage Mechanism

Abstract: One of the most complex and important features of both the nervous and immune systems is their data storage and retrieval capability. Both systems encounter a common and complex challenge on how to overcome the cumbersome task of data management. Because each neuron makes many synapses with other neurons, they are capable of receiving data from thousands of synaptic connections. The immune system B and T cells have to deal with a similar level of complexity because of their unlimited task of recognizing foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 103 publications
(144 reference statements)
0
17
0
Order By: Relevance
“…First, recent work demonstrated that some DNA methylation sites appear to be highly dynamic and far less stable compared to those reported for the GR, indicating that not all DNA methylation sites are able to support long-term changes in transcriptional regulation (Miller et al, 2008; Novikova et al, 2008). Second, many other epigenetic processes such as RNA editing (Lalli et al, 2003; Qureshi and Mehler, 2009; Tan et al, 2009), DNA recombination (Habibi et al, 2009), and a host of other chromatin remodeling mechanisms (Lund and van Lohuizen, 2004; Payer and Lee, 2008) are capable of mediating long-lasting stable alteration in cell fate and function. Third, long-term programming of gene expression is not necessary in order for events early in life to modify brain function in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…First, recent work demonstrated that some DNA methylation sites appear to be highly dynamic and far less stable compared to those reported for the GR, indicating that not all DNA methylation sites are able to support long-term changes in transcriptional regulation (Miller et al, 2008; Novikova et al, 2008). Second, many other epigenetic processes such as RNA editing (Lalli et al, 2003; Qureshi and Mehler, 2009; Tan et al, 2009), DNA recombination (Habibi et al, 2009), and a host of other chromatin remodeling mechanisms (Lund and van Lohuizen, 2004; Payer and Lee, 2008) are capable of mediating long-lasting stable alteration in cell fate and function. Third, long-term programming of gene expression is not necessary in order for events early in life to modify brain function in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that L1s in cooperation with RAG1 play a role in increasing neuronal diversity, which is required for memory storage and different complex thought processes in the brain ( Fig. 1) (Habibi et al, 2009). The important question is whether our immune cells could fight with different types of foreign antigens threatening our body, without the presence and functions of mobile DNA elements (Fugmann, 2010).…”
Section: Tes and Evolution Of Essential Cellular Mechanismsmentioning
confidence: 99%
“…Neurons and glial cells are not only able to synthesize different cytokines and chemokines but can also respond to them via a diverse set of cytokine receptors that are expressed on the surface of cells localized in different brain regions. Several immune mediators, including IL-1β, IL-6, TNF-α, and IFN-γ, appear to regulate synaptic transmission, and the receptor for IFN-γ is localized at certain synapses (Habibi et al, 2009). A subset labeled as neuropoietic cytokines plays several key roles in normal brain development, contributing to the proliferation, differentiation and ultimate fate of neural precursor cells; neuronal and glial cell migration and survival; and activity-dependent synaptic plasticity (Stolp, 2012).…”
Section: Immune-mediated Animal Models Of Tsmentioning
confidence: 99%